Serum and Glucocorticoid-Inducible Kinase 1 (SGK1) in NSCLC Therapy - Ilaria Guerriero; Gianni Monaco; Vincenzo Coppola; Arturo Orlacchio (MDPI AG, 2020)
Non-small cell lung cancer (NSCLC) remains the most prevalent and one of the deadliest cancers worldwide. Despite recent success, there is still an urgent need for new therapeutic strategies. It is also becoming increasingly evident that combinatorial approaches are more effective than single modality treatments. This review proposes that the serum and glucocorticoid-inducible kinase 1 (SGK1) may represent an attractive target for therapy of NSCLC. Although ubiquitously expressed, SGK1 deletion in mice causes only mild defects of ion physiology. The frequent overexpression of SGK1 in tumors is likely stress-induced and provides a therapeutic window to spare normal tissues. SGK1 appears to promote oncogenic signaling aimed at preserving the survival and fitness of cancer cells. Most importantly, recent investigations have revealed the ability of SGK1 to skew immune-cell differentiation toward pro-tumorigenic phenotypes. Future studies are needed to fully evaluate the potential of SGK1 as a therapeutic target in combinatorial treatments of NSCLC. However, based on what is currently known, SGK1 inactivation can result in anti-oncogenic effects both on tumor cells and on the immune microenvironment. A first generation of small molecules to inactivate SGK1 has already been already produced.